2020
DOI: 10.3390/jcm9082670
|View full text |Cite
|
Sign up to set email alerts
|

Role of Type2 Inflammatory Biomarkers in Chronic Obstructive Pulmonary Disease

Abstract: Airway inflammation in chronic obstructive pulmonary disease (COPD) is typically thought to be driven by Type1 immune responses, while Type2 inflammation appears to be present in definite proportions in the stable state and during exacerbations. In fact, some COPD patients showed gene expression of Type2 inflammation in the airway, and this subset was associated with the inhaled corticosteroid (ICS) response. Interestingly enough, the relationship between COPD and diseases associated with Type2 inflammation fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 171 publications
(259 reference statements)
1
22
0
Order By: Relevance
“…Subsequent infiltration of eosinophils in the airways of COPD patients regulates an immunoglobulin E (IgE)dependent mechanism, which is considered an important part of Th2 cell cytokine production process, resulting in an imbalanced production of Th2 cells that may cause an irregular Th1/Th2 ratio and interleukin-17/IgE ratio. [36][37][38] We also observed a lower medical cost in eosinophilic AECOPD patients. These findings are consistent with those of previous studies despite different clinical settings, enrolment criteria, and definitions of disease severity and exacerbation.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Subsequent infiltration of eosinophils in the airways of COPD patients regulates an immunoglobulin E (IgE)dependent mechanism, which is considered an important part of Th2 cell cytokine production process, resulting in an imbalanced production of Th2 cells that may cause an irregular Th1/Th2 ratio and interleukin-17/IgE ratio. [36][37][38] We also observed a lower medical cost in eosinophilic AECOPD patients. These findings are consistent with those of previous studies despite different clinical settings, enrolment criteria, and definitions of disease severity and exacerbation.…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, in this study, similar difference of LOS was observed in the subgroup analysis of elderly patients but not middle‐aged patients. A potential explanation for this difference between the eosinophilic and non‐eosinophilic group is that high eosinophil counts are associated with high levels of T‐helper cell type 2 (Th2) inflammation, which implies more eosinophilic airway inflammation but less bacterial inflammation 36 . Increasing evidence in recent years has shown that eosinophilic airway inflammation might play an important role in pathogenesis of COPD 37 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 3 In recent years, there have been a large number of studies on the role of type 2 biomarkers in COPD, including eosinophils, IgE and FeNO 50. 4 Nitric oxide (NO) is biosynthesized from L-arginine and oxygen by the enzyme NO synthase (NOS) endogenously, fractional concentration of exhaled nitric oxide at a flow rate of 50mL/s (FeNO 50 ) is a known marker of airway inflammation. As a noninvasive, convenient and highly reproducible method for assessing airway inflammation, FeNO measurement has been used to evaluate type 2 inflammation of asthma and guide anti-inflammatory treatment.…”
Section: Introductionmentioning
confidence: 99%